INFLUENCE OF ROTATING SPEED, LOAD, AND LUBRICANT VISCOSITY OF ROLLING BEARING ON SHOCK PULSE VALUE, VIBRATION, AND TEMPERATURE - (NIM : 131 05 013); Pembimbing : Dr. Ir. Zainal Abidin, KHUSCHANDRA
Bearing is very important component in rotating machine. It is a critical component so machine can operate. However, sometimes bearing can be damaged before itÃ‚Â’s design lifespan is reached. This damage can be caused by poor clearance, poor lubrication, overload, or others non ideal operating condition on bearing. This final project is about characteristics of good, wear, and damaged bearing as changing of load, rotating speed, and lubricant viscosity. The objective is knowing the characteristics of shock pulse value, vibration, and temperature on rolling bearing in terms of changing of load, rotating speed, and lubricant viscosity. Based on these testing results of the three tested bearings, it can be concluded that repeatability and hysteresis of shock pulse values are better than vibration values. Both shock pulse values and temperatures increase along with increasing rotating speed or load. Together with increasing damages, dBm, LR, and HR tent to increase too. dBc of damaged bearing is lower than wear bearing at rotating speed below 1000 RPM, whereas at rotating speed above 1000 RPM, dBc of damaged bearing is higher than wear bearing. In addition, both dBm-dBc and LR-HR for good and wear bearing have no significant difference. On the other side, both of them are significantly increased for damaged bearing. Vibration values have no consistent tendency along with increasing damages. Shock pulse spectrums of wear bearing show the characteristic of mechanical looseness, whereas shock pulse spectrums of damaged bearing show the characteristic of outer race damage. Vibration spectrum of wear and damaged bearing show characteristic of outer race damage.